Vulgatos prielinksninių konstrukcijų santykis su inesyvu J. Bretkūno „Evangelijos pagal Luką“ vertime - Gelumbeckaitė, Jolanta (Baltistica, 1996)
ON THE RELATION OF THE VULGATA’S PREPOSITIONAL PHRASES WITH THE TRANSLATION OF THE GOSPEL ACCORDING TO LUKE BY JONAS BRETKŪNAS J. Bretkūnas translated the Bible from different German editions of M. Luther’s Bible, but the Gospel according to Luke was translated from Latin and afterwards corrected with reference to the version of M. Luther. In order to establish the relation of the prepositional phrases of the Gospel according to Luke with J. Bretkūnas’ translation all the correspondences of Latin prepositional phrases were classified according to the forms of the Latin text. The unprepositional case forms in the 16th century were still used in certain meanings in the cases where nowadays the prepositional phrases predominate. The said status is quite obviously observed in J. Bretkūnas’ translation where 1/4 of Latin prepositional phrases are translated using different variants of the postpositional Locative, i.e. Innesive, Illative, Adessive, Allative. In the present paper we discuss the Inessive. 219 Latin prepositional phrases are translated using the Inessive. The following relations between the Vulgate’s prepositional phrases and the unprepositional Inessive can be stated: 1. in + Abl mostly corresponds to the Lithuanian Iness. 2. in+Acc. is translated by using the Iness. only in the cases where verbs with the indirective valency are used by J. Bretkūnas. 3. When denoting the processes in the mind of person(s) the Iness. corresponds to prepositional phrases apud+Acc, inter + Ace, intra + Ace, and partly in +Abl. 4. The Iness. with temporal meanings is used in translation of prepositional phrases in+Abl., where the noun denotes temporal concepts. The correspondences show the synonymy of the temporal Iness. and the Instrumental in Old Lithuanian. 5. The influence of the in + Abl. or in+Acc. on the use of Iness., denoting the inner state of person(s) or its extent, is noted. 6. The use of the Iness. to translate in+Abi limitationis is due to the Latin influence as well.